Influence of intrapersonal and interpersonal religiosity on materialistic attitudes among youths in India: a structural equation modelling approach. (5th June 2020) - Sadiq, Muhammad Ahsan; Ansari, Lubna; Gupta, Prashant
The paper aims at studying the role of intrapersonal and interpersonal religiosity as a predictor of materialistic attitudes (possession, non-generosity and envy) among youths in India using structural equation modelling. Data is collected from 252 students of public-funded central universities in India using simple random sampling. Intrapersonal religiosity is found to predict possession and non-generosity dimensions of materialistic attitudes. In contrast, Interpersonal religiosity is found to be influencing only possession dimension of materialism. Surprisingly, interpersonal religiosity was found to be positively correlated with envy attitudes of materialism among youths in India. The research is expected to help marketers and policymakers to refine their strategies for religious youths in India accordingly.